Karta si︠e︡vernago Ledovitago okeana otʺ Enĭseiskago zaliva do ustʹi︠a︡ ri︠e︡ki I︠A︡ny / Sostavlena sʺ Russkikhʺ opiseĭ 1734-42 i 1821-23 g.g. izdana Gidrograficheskimʺ Departamentomʺ Morskago Ministerstva vʺ 1874 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1874)
Relief shown by form lines. Depths shown by soundings.; Title translation: Map of the Arctic Ocean from the Yenisei Gulf to the mouth of the Yana River.; Greenwich and Pulkovo meridians given.; "Masshtab: 1/2,100,000 ili 50 versti︠e︡ v 1 a. d." = Scale 1/2,100,000 or 50 versts in 1 English inch.; "No. 229" -- bottom right margin Grayscale; 1:2,100,000